Loss of Eml1 alters microtubule-associated protein networks in mouse brain heterotopia - Berfu Nur Yigit; Dilaray Tufekci; Valeria Viola; Busra Aytul Kirim; Donia Zaidi; Fiona Francis; Nurhan Ozlu (Communications Biology)
Abstract Microtubules and microtubule-associated proteins are critical regulators of cerebral cortex development, and their defects can lead to severe cortical malformations. EML1/Eml1 (Echinoderm microtubule-associated protein-like 1) is a microtubule-binding protein whose mutations cause subcortical heterotopia in both humans and mice. While perturbations of Eml1 in neural progenitor cells have been associated with defects in cilia and progenitor cell detachment from the ventricular zone, the regulatory role of Eml1 at the protein level remains understudied. To reveal global changes in the absence of Eml1, we perform a comparative proteomic analysis of the cortices and neural progenitor cells of Eml1 conditional-knockout mice during cerebral cortex development. Our comprehensive analyses reveal that Eml1 depletion causes significant downregulation of multiple centrosomal and spindle proteins in neural progenitor cells. The absence of Eml1 significantly reduces microtubule polymerization and stability. Several microtubule-associated proteins, including Eml4 and Septins, lose their affinity with microtubules in the absence of Eml1. Our findings support the central role of Eml1 in the regulation of microtubules and provide a valuable resource for the investigation of the underlying mechanisms of heterotopia-based pathophysiological conditions.